Theoretical trends explaining school violence among secondary school students (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2020)
Human society has known the phenomenon of violence since ancient times and to varying degrees. , Which hinders the educational and educational work expected of the school, and makes it an inappropriate environment to achieve the educational objectives assigned to it, has spread among students specifically, and has become a concern for many parents and students.In this context, this study seeks to identify the most important theories that dealt with the interpretation of violent behavior in order to complicate behavior and change, and identify what is and types of school violence. The descriptive approach was adopted to reach some recommendations and suggestions to alleviate the phenomenon of school violence عرف المجتمع البشري ظاهرة العنف منذ القدم وبدرجات متفاوتة، و عدَ العنف ظاهرة مركبة لها جوانبها الاجتماعية والنفسية والاقتصادية، فهو سلوك يمكن أن يكون مكتسب من البيئة الاجتماعية التي يحيا فيها الفرد، ويندرج مفهوم العنف المدرسي تحت مفهوم العنف بشكل عام الذي يعد من أكثر المشكلات سلبية وانتشاراً، والذي يعيق العمل التربوي والتعليمي المتوقع من المدرسة، ويجعلها بيئة غير ملائمة لتحقيق الأهداف التربوية المنوطة بها، وقد انتشر بين الطلاب تحديداً، وأصبح يشكل مصدر قلق للكثير من أولياء الأمور والطلاب. وفي هذا الإطار تسعى هذه الدراسة إلى التعرف على أهم النظريات التي تناولت تفسير سلوك العنف وذلك لتعقد السلوك وتغيره، والتعرف على ماهية العنف المدرسي وأنواعه. حيث تم اعتماد المنهج الوصفي ليتم بعدها التوصل إلى بعض التوصيات والمقترحات للتخفيف من ظاهرة العنف المدرسي.